A new species of Bufoides Pillai and Yazdani 1973 (Amphibia: Bufonidae) from Mizoram (India) and the delimitation of the distribution range of Bufoides meghalayanus (Yazdani & Chanda 1971) to the Khasi hills, Meghalaya (India) - R.S. NAVEEN; BENJAMIN TAPLEY; S.R. CHANDRAMOULI; PHILLIP A. JERVIS; S. BABU; A.B. MEETEI; P.V. KARUNAKARAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Naveen RS, Tapley B, Chandramouli SR, Jervis PA, Babu S, Meetei AB, Karunakaran PV. 2023. A new species of Bufoides Pillai and Yazdani 1973 (Amphibia: Bufonidae) from Mizoram (India) and the delimitation of the distribution range of Bufoides meghalayanus (Yazdani & Chanda 1971) to the Khasi hills, Meghalaya (India). Biodiversitas 24: 4617-4627. The Oriental toad genus Bufoides currently comprises two species: Bufoides meghalayanus and B. kempi. Populations of Bufoides from Mizoram were previously considered to be conspecific with Bufoides meghalayanus, although it has been hypothesized that these populations could represent an undescribed species. An uncorrected p-distance at the 16S rDNA gene between the Mizoram population and each of the two congeneric species was 2.74-3.0% and 3.5% for B. meghalayanus and B. kempi respectively. We describe the population from Dampa Tiger Reserve, Mizoram, as new based on molecular from two specimens and morphological data from two adult males and one adult female. We confirm that B. meghalayanus is endemic to the Khasi Hills in Meghalaya and it does not occur in Mizoram. The new species from Mizoram differs from congeneric species by differences in interdigital webbing, coloration, skin tuberculation and the presence of ovoid, tuberculated and depressed parotoid glands. Like other Bufoides species, it is a microhabitat specialist and utilizes streamside rock crevices as refugia, which might make it vulnerable to changes in habitat. The new species is currently only known to occur in Dampa Tiger Reserve and it is probably range-restricted and likely meets the International Union for Conservation of Nature’s criteria for being assessed as Critically Endangered.